EFFICACY OF IVABRADINE AND VERAPAMIL IN PATIENTS WITH DIASTOLIC HEART FAILURE CAUSED BY LEFT VENTRICLE IMPAIRED RELAXATION - K. G. Adamyan; A. L. Chilingarian (Рациональная фармакотерапия в кардиологии)
Aim. To compare ivabradine (IB) and verapamil (VP) effects on left ventricle (LV) diastolic function in patients with diastolic heart failure (DHF) caused by left ventricle impaired relaxation.Methods. It was comparative randomized study. 238 patients (190 men, 48 women; aged 63±10 y.o.) with DHF were randomized in two groups to receive IB (7,5 mg bid, n=119) or VP (240 mg o.d., n=119). Echocardiography (EchoCG) indices, total ischemic burden (TIB) and N-terminal fragment of pro-brain natriuretic peptide (NT-pro-BNP) were evaluated initially and after 1, 3, 6 and 12 months of therapy.Results. After 3 months of therapy some EchoCG parameters (E/A, transmitral E wave deceleration time [EDT]) as well as TIB improved more significantly in IB group. After 6 months in IB group in comparison with VP group additional differences appeared (midwall fractional shortening; E/Em of lateral mitral annulus – 8,6±4,7 and 12,3±4,7, respectively, p<0,05; NT-pro-BNP – 91,7±4,3 pg/ml and 128±7,6 pg/ml, respectively, p<0.01) or became stronger (TIB, E/A and EDT). The differences persisted after 12 months of follow up. Besides a number of patients required hospitalization were less in IB group in comparison with VP group (11 vs 19, respectively, p<0.05).Conclusion. Both IB and VP improved diastolic function and reduced heart rate, ischemia time, NT-pro-BNP levels and hospitalization rate in patients with DHF. However, IB compared with VP has more prominent effect on these parameters.